UJI KUALITAS FISIS PENGOLAHAN LIMBAH PLASTIK MENJADI BAHAN BAKAR ALTERNATIF - Nurhalima, Nurhalima; Rahmaniah, Rahmaniah; Iswadi, Iswadi (JFT : Jurnal Fisika dan Terapannya, 2015)
This study aims to determine whether the plastic waste can be used as an alternative fuel and to determine the physical quality of alternative fuels plastic waste generated before distillation and after distillation. This study is done the combustion process using a tool designed himself. After the burning process, the oil obtained is done by testing physical parameters are density, viscosity and caloric value. The results showed that the physical quality of alternative fuels, namely plastic waste For this type of plastic PET, HDPE, LDPE, PVC and PP in density test results obtained before and after distillation not meet fuel standards. The results obtained on testing the viscosity value for the type of plastic PET, LDPE, PP and PVC before distillation including kerosene fuel standards. Whereas For this type of plastic HDPE and PP after distillation including kerosene fuel standards. While the test results obtained calorific values for the type of plastic PET, HDPE, PVC, LDPE and PP before and after distillation not meet fuel standards.